If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = 10x + -7 Reorder the terms: 3 + 5x = 10x + -7 Reorder the terms: 3 + 5x = -7 + 10x Solving 3 + 5x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 3 + 5x + -10x = -7 + 10x + -10x Combine like terms: 5x + -10x = -5x 3 + -5x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 3 + -5x = -7 + 0 3 + -5x = -7 Add '-3' to each side of the equation. 3 + -3 + -5x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = -7 + -3 -5x = -7 + -3 Combine like terms: -7 + -3 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= | | 21x^4=2+x^2 | | 2-8x/1 | | 4(x+5)=3(x-6)+x | | -2(7-y)+4=44 |